Performance evaluation of production structures in agricultural holdings: Case study - Adrian Turek Rahoveanu; Maria Magdalena Turek Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The performance of production structures in agriculture is determined by a complex of factors, the most important are: the natural potential of agricultural holdings, financial resources necessary to purchase inputs, ensuring balance in the allocation of factors of production, technical and technological potential, the existing workforce and the readiness of the farm manager. Based on these considerations we want in this paper to analyze the aspectes defining application of performance management in order to develop sustainable production structures, increase competitiveness of farms, farmers' income stabilization and Romanian rural development.
Keywords: 330; production structure; management; efficiency; competitiveness